On countryside roads to national identity: Japanese morning drama series (asadora) and contents tourism. Issue 1 (2nd January 2020) - Scherer, Elisabeth; Thelen, Timo
Abstract: Since the 1960s, NHK's morning drama series ( asadora ) have become known as a popular and quasi-institutionalised serial format of Japanese TV broadcasting. They attract millions of viewers by telling stories of female protagonists struggling to achieve personal fulfilment. At the same time, they also function as tools to spread certain forms of national identity, which are often linked to conservative concepts of an ideal Japanese lifestyle and anchored in a nostalgic rural landscape. Using the example of 2015's asadora Mare, we investigate how these two crucial aspects are implemented in the series' narrative and production. Furthermore, we link our observations to the domain of 'contents tourism'; this type of Japanese media-induced tourism recently gained significant attention from regional decision-makers working towards local revitalisation. By investigating contents tourism activities in Mare's context, the rural city of Wajima in the Noto Peninsula, we aim to understand how the media-touristic negotiation between real and imaged landscapes works and how that process influences consumers as well as locals. Our study provides a previously missing link between the qualitative analysis of media content and the examination of contents tourism in order to achieve a broader sociocultural perspective on this phenomenon.